The Effect Of Endorphin Massage On Milk Production In Postpartum Mothers - Niken Bayu Argaheni (Poltekkes Kemenkes Surakarta, 2021)
Background: Low milk production in the first few days after delivery becomes constraints in early breastfeeding. The purpose of this research is to find out effect of endorphin massage on milk production in postpartum mothers. Methods: Systematic review using the database: Google Scholar. The search results that meet the article criteria between 2017-2021, having minimum 20 sample, using keywords “massage, endorphin, ASI” are then analyzed for articles. Results: From 17 article extracted, it showed that milk production can be improved by massage techniques such as endorphin massage. Conclusion: To increased breast milk, it is advisable for postpartum mothers using massage therapy such as endorphin massage.